Bioclimatic Design of Low-Cost Rural Dwellings - Bera, Mahadev; Nag, Pranab Kumar (Frontiers in Built Environment, 2022)
The bioclimatic design is a crucial strategy to achieving the eco-friendliness, human-friendliness, and energy-friendliness of the built environment. The building patterns, materials, innovation, and use depend on the inhabitant's choices, lifestyle, and economic viability. The study focused on examining bioclimatic components of low-cost dwellings in rural coastal environments in eastern India. A survey questionnaire administered to about 1300 respondents from 15 villages (classified as remote rural, rural and semi-urban) yielded their perception of different dwelling environments issues. The statistical analysis of bioclimatic dimensions indicated a significant difference among the dwellings. The low-cost mud houses of the remote rural and rural areas in coastal regions often follow local practices. Besides, different dimensions covered in the survey provided insights for the comparative evaluation of different categories of dwelling units. The principal components analysis (PCA) identified the clusters and component structures of the built environment characteristics responded by the villagers as their perception of the dwellings. The PCA yielded three components (a) interior design (PC1, building form, partitioning of rooms, type and materials of the wall, roof and window), (b) innovation of built environment (PC2, building envelope, insulation and sanitation facilities), and (c) natural ventilation priority (PC3, window design, window opening and glaze material), which together explained 69% of the total variance. The Psychrometric Chart provided in ASHRAE 2005 identifies passive design strategies in constructing dwellings to improve residents' yearly total thermal comfort hours in hot and humid regions. The relative contributions to thermal comfort hours are sun shading of windows (25.5%), passive solar direct gain high mass (6.2%), passive solar direct gain low mass (0.4%), high thermal mass, including night flushed (4.3%), direct and two-stage evaporative cooling (4.3%), natural ventilation and fan-forced ventilation cooling (2.2%).